The Effect of Oral Feedback in Secondary Classrooms on Arab Female Students’ Acquisition of English Past Tense - Saad, Doa Mostafa (2013)
The present study investigated the effect of oral feedback on Arab female students’ uptake and acquisition of English regular and irregular past tense in the context of secondary EFL classrooms in the UAE. It adopted a mixed methods approach in which qualitative and quantitative data was collected. In the qualitative phase of the study, the interaction between 2 EFL teachers and 48 EFL high-school female students in fourteen lessons was video recorded. The frequency and distribution of the teachers’ feedback types as well as the students’ uptake were identified and coded using Lyster and Ranta’s (1997) corrective feedback model. Video recordings were followed by stimulated-recall interviews with four participants from each class to check their noticing of the teachers’ corrective feedback. Interviews with the participating teachers were also conducted. The quantitative phase included measuring the students’ past tense accuracy rate in three tests: pretest, posttest, and delayed test. The findings of this study indicate that a variety of feedback types was used in the EFL classroom with prompts (72.7%) exceeding the number of recasts (23.3%). The study also shows that elicitations and metalinguistic feedback were the most successful in eliciting student-generated repair with a 64.7% and 44% respectively. Recasts were found to be the least noticeable with only 12% resulting in successful uptake. Interviews with students reveal that prompts were the most noticeable and favored feedback type. Results of one-way repeated measures ANOVA show an increase in the overall past tense accuracy scores across time. A significant difference was found between the regular past tense scores of the class which predominantly received prompts. The results of this study confirm the positive impact of feedback on the acquisition of English past tense.